2004
DOI: 10.3917/cca.102.0099
|View full text |Cite
|
Sign up to set email alerts
|

Le ratio market-to-book et la reconnaissance des immatériels – une étude du marché français

Abstract: RésuméCet article apporte une contribution aux différentes solutions avancées pour expliquer l'écart constaté entre la valeur comptable et la valeur de marché des sociétés. Notre hypothèse est qu'il peut être en partie expliqué par le fait que les éléments immatériels ne sont pas correctement représentés dans les états financiers. Nos résultats indiquent un lien statistique entre le goodwill inscrit à l'actif et le ratio marketto-book. En revanche, aucun lien statistiquement significatif n'a été mis en évidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
5
17
0
7
Order By: Relevance
“…Goodwill is also significant for the two sub -periods (pre-and post-fair value) at the conventional threshold of 1%. This result is consistent with studies of Peasnell and Mather (1991), Seethamraju (2003) and Cazavan (2003) which stipulate an existence of a positive and significant correlation between goodwill and stock return. Taken together, the historical cost show clearly that with the application of the principle of fair value only financial assets become insignificant.…”
Section: Multivariate Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…Goodwill is also significant for the two sub -periods (pre-and post-fair value) at the conventional threshold of 1%. This result is consistent with studies of Peasnell and Mather (1991), Seethamraju (2003) and Cazavan (2003) which stipulate an existence of a positive and significant correlation between goodwill and stock return. Taken together, the historical cost show clearly that with the application of the principle of fair value only financial assets become insignificant.…”
Section: Multivariate Analysissupporting
confidence: 82%
“…Moreover, until the nineties, research studies in the US prove the existence of a significant association between financial assets and the market value of the company (Hassan, Percy and Jenny Stewart, 2006). For goodwill, research studies have shown the existence of a positive and significant correlation between the accounting data and the stock price and therefore the stock return (Mather and Peasnell 1991;Seethamraju 2003, andCazavan 2003). Therefore, by referring to the above, we will argue that the informational content of accounting data (EPS, EQ, financial assets and goodwill) would be more appropriate under the principle of fair value than the historical cost.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Ratio of the total market capitalization (share price times number of outstanding common shares) to book value of net assets, used as a proxy for stock market performance (Sougiannis, 1994;Firer and Williams, 2003;Cazavan-Jeny, 2004 (Lev): measured by the ratio of book value of total assets to book value of common equity (Lev and Sougiannis, 1996).…”
Section: Mbmentioning
confidence: 99%
“…Some studies also focussed on the problem of IC measurement not being recorded in financial statements (Stewart, 1997;Pulic, 1998Pulic, , 2004Gu and Lev, 2003;Chen et al, 2004). Finally, a number of studies were related to the validation of IC in a decision-making context, notably in terms of its usefulness to investors on a capital market (Lev and Sougiannis, 1996;Cazavan-Jeny, 2004;Casta et al, 2005;Lev et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided statistical evidence that the market attaches relevance to the goodwill recognized by companies, such as those from Jennings et al (1996), Henning et al (2000), Godfrey and Koh (2001), Dahmash et al (2009), Oliveira et al (2010), and Cazavan-Jeny (2004.…”
Section: Goodwill Per Sharementioning
confidence: 99%